The relationship between positive workplace gossip and job satisfaction: The mediating role of job insecurity and organizational identity - Wang, Dawei; Niu, Zhaoxiang; Sun, Chongyu; Yu, Peng; Wang, Xiaolong; Xue, Qihui; Hu, Yixin (Frontiers in Psychology, 2022)
From the perspective of social information processing theory and social identity theory, this study recruited 1267 employees as participants to explore the relationship between positive workplace gossip and job satisfaction and the role of job insecurity and organizational identity in this relationship. The results showed that there was a significant positive correlation between positive workplace gossip and job satisfaction. Furthermore, job insecurity and organizational identity independently mediated the relationship between positive workplace gossip and employee job satisfaction. In addition, job insecurity and organizational identity played a serial mediating role in the relationship between positive workplace gossip and job satisfaction. The results of the study shed light on how job insecurity and organizational identity were associated with the process of the positive workplace gossip-job satisfaction relationship. Based on the findings, implications and avenues for future research were discussed.